Impact of Patient Subtype and Surgical Variables on Abdominoplasty Outcomes: A 12-Year Massachusetts General Hospital Experience. Issue 5 (November 2017) - Seth, Akhil K.; Lin, Alex M.; Austen, William G.; Gilman, Robert H.; Gallico, Gregory G.; Colwell, Amy S.
Abstract : Background: The traditional abdominoplasty is one of the most common surgical procedures performed. This study evaluates the impact of different surgical techniques and clinical patient factors on abdominoplasty outcomes. Methods: A retrospective review of consecutive patients undergoing abdominoplasty was performed. Results: Seven hundred seventy-nine patients with a mean age of 43.7 years and a body mass index of 27 kg/m 2 underwent abdominoplasty. The majority were women (92.9 percent), and massive weight loss was present in 34.8 percent. Abdominoplasty techniques included traditional (59.4 percent), belt lipectomy (17.9 percent), fleur-de-lis (16.4 percent), umbilical float (9.2 percent), and mini-abdominoplasty (2.8 percent). Half of the study population [ n = 384 (49.3 percent)] had concurrent surgical procedures. Total complications (23.0 percent) consisted primarily of wound- and scar-related complications (15.3 percent). Approximately 60 percent of patients received heparin chemoprophylaxis, with overall thromboembolic and hematoma rates less than 1 percent. Univariate analysis revealed that massive weight loss ( p = 0.04), fleur-de-lis ( p = 0.03) or belt lipectomy ( p = 0.05) techniques, and concurrent medial thigh lift ( p < 0.001) all significantly increased complications. Previous scars, amount of weight loss, operative time, liposuction, and other concurrent procedures did not affect total complications. Male sex (OR, 1.96; p = 0.04), fleur-de-lis technique (OR, 1.71; p = 0.04), and medial thigh lift (OR, 3.3; p < 0.001) were independent risk factors for total postoperative complications. Conclusion: This study demonstrates that abdominoplasty alone or in combination with liposuction and aesthetic breast surgery can be performed safely, with an acceptable complication profile. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.